Upaya Pencegahan Sexual Violence Pada Remaja Sekolah di Merawang Kabupaten Bangka - Sujadmi Sujadmi; Luna Febriani; Herdiyanti Herdiyanti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2018)
The right for good life such as education and peace are one of them. They often experience sexual violence and abuse. The case of sexual abuse faced by them increases. This requires special attention to solve and prevent the case. The perpetrators mostly are adults and even from the member of family. The educators are expected to be the role model for the pupils not otherwise. To tackle the issue, it requires the knowledge and a strategy to prevent the mentioned case. Sex education can be one of the solutions to prevent the mentioned case experienced by the children and teenage girl so that they are able to identify the types of sexual violence. Extension can be conducted as the form of education. It can be through providing the flyers and stickers to teenagers and to the other people. High school becomes its target. The extension was conducted in SMAN 1 Merawang. The keynote speaker of the events were the expert from educational and psychological field. It was expected by having enough knowledge on types of sexual violence, parents, students and other parts of society were able to protect themselves from the potential mentioned case.